Development of Android-based interactive applications to stimulate children's cognitive development - Andi Agusniatih; Ika Anggraini As Sayyidah; Shofiyanti Nur Zuama; Amrullah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Early childhood cognitive development requires engaging learning media. However, many PAUD classrooms still rely on monotonous activities that reduce children's motivation and limit cognitive progress. This study aimed to develop an Android-based interactive learning application to stimulate early childhood cognitive development, particularly in recognizing colors, geometric shapes, and sizes. The study used a research and development method based on the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The population comprised children at RA Al Ikhlas Birobuli. Participants for the classroom trial were selected through purposive sampling, focusing on children who took part in the learning activities during the implementation stage. Data were collected using observation sheets to measure learning engagement and cognitive performance, expert validation questionnaires to assess media and material feasibility, and cognitive tests in the form of a pretest and posttest to measure learning outcomes. Expert validation results indicated that the application was highly feasible, with a media feasibility score of 95% and a material feasibility score of 92%. Classroom implementation showed a significant improvement in children’s cognitive abilities, as indicated by higher posttest scores than pretest scores and a p-value of 0.000. The application includes interactive features such as visual animations, sound effects, game-based tasks, and a reward system, which increased engagement and motivation and supported constructivist principles that emphasize active and multisensory learning. In conclusion, the Android-based interactive application is effective, practical, and innovative for supporting early childhood cognitive development. It is recommended that PAUD teachers use this application as complementary learning media. Future studies should involve larger and more diverse samples and evaluate long-term learning retention and usability across different devices.